Post-traumatic Hemothorax: Management in a Limited-medium Structure - AD, Jonatana; VB, Razafindraibe; CP, Rahantasoa Finaritra; F, Randrianambinina; LH, Samison; AH, Rakotoarijaona; HJL, Rakotovao (International Journal Papier Advance and Scientific Review, 2020)
Post-traumatic hemothorax is common in young adults in the context of road accidents. Explorations of the lesions may be limited by the technical platform. The objective of our study is to discuss the difficulty of managing post-traumatic hemothorax in a limited-medium structure. This was a 20-month retrospective study (01 May 2018-31 December 2019), involving 38 patients treated for post-traumatic hemothorax, whether or not associated with pneumothorax, in the general surgery department of the CHU Analankinina Toamasina. The hospital frequency was 1.66%, with a mean age of the patients of 31.89 years, and a male predominance (73.68%). The main provider of hemothorax was the civil liability accident (52.63%). Chest X-rays were performed in almost all patients (94.74%). Complications had been found in 4 patients with secondary surgery, with favorable outcomes. The frequency of hemothorax is constantly increasing in Madagascar, where the civil liability accident is the main cause. Chest X-ray remains the most accessible examination to be carried out in emergency. An early and efficient thoracic drainage generally ensures a favorable evolution without after-effects.